PAF15–PCNA exhaustion governs the strand-specific control of DNA replication - Gita Chhetri; Sugith Babu Badugu; Narcis-Adrian Petriman; Mikkel Bo Petersen; Aylin Seren Güller; Nora Fajri; Manon Coulée; Ganesha Pandian Pitchai; Jan Novotný; Frederik Tibert Larsen; Andreas Fønss Møller; Morten Frendø Ebbesen; et al. (Nature, 2026)
Abstract Eukaryotic genome replication is surveyed by the S-phase checkpoint, which coordinates sequential origin activation to prevent the exhaustion of poorly defined, rate-limiting replisome components 1–3 . Here we show that excessive origin firing saturates chromatin-bound proliferating cell nuclear antigen (PCNA)—a sliding clamp for DNA polymerase processivity and Okazaki fragment processing 4 —thereby restricting further PCNA loading and lagging-strand synthesis when checkpoint control is lost. PCNA-associated factor 15 (PAF15) emerges as a dosage-sensitive regulator of this process 5–9 . During unperturbed S phase, the entire soluble PAF15 pool binds to chromatin, leaving no reserve to stabilize PCNA under conditions of excessive origin activation. PAF15 binds to PCNA specifically on the lagging strand through a high-affinity PIP motif and occupies the DNA-encircling channel, protecting the clamp and associated enzymes from premature unloading by the ATAD5–RFC complex. Conversely, overexpression of PAF15 or forced redistribution to the leading strand disrupts replisome progression and induces cell death. These detrimental effects are mitigated by Timeless–Claspin, which blocks PAF15–PCNA binding on the leading strand. E2F4-mediated repression fine-tunes PAF15 expression to ensure optimal dosage and strand specificity. These findings reveal a previously unrecognized replisome constraint: when PAF15–PCNA assemblies are exhausted, the S-phase checkpoint globally restricts origin activation, linking a strand-specific rate-limiting mechanism to global replication dynamics.